Kompetensi Manajerial Kepala Sekolah dalam Meningkatkan Prestasi Non Akademik Siswa SMP - Karlina Yulista; Yulia Tri Samiha; Ahmad Zainuri (Studia Manageria, 2020)
The purpose of this study was to find out how the students' non-academic achievement in the religious field of reading and writing al-quran and da'i / da'iyah. The type of research used is qualitative research. The research instrument used documentation, interviews, observation and triangulation. Then the data analysis used reduction, data presentation and data verification. The results of the study concluded that 1) planning, namely the principal carried out: formulating a vision and mission, compiling a strategic plan, compiling an annual activity plan and compiling an activity budget; 2) Student Management, namely: Management of Religious activities, Grouping and orientation, Guidance and reward systems / rewards for outstanding students; 3) Monitoring and evaluation includes: preventive supervision and collective supervision, and evaluation includes; student attendance and control books; 4) The obstacles faced by the principal in improving students' non-academic achievement, namely; minimal funding, lack of spiritual guidance coordinators and undisciplined students participating in religious activities to read and write Al-Qur'an and da'i / da'iyah.